2019
DOI: 10.1002/jmri.26748
|View full text |Cite
|
Sign up to set email alerts
|

Proton density fat fraction MRI of vertebral bone marrow: Accuracy, repeatability, and reproducibility among readers, field strengths, and imaging platforms

Abstract: Background Chemical shift‐encoding based water‐fat MRI is an emerging method to noninvasively assess proton density fat fraction (PDFF), a promising quantitative imaging biomarker for estimating tissue fat concentration. However, in vivo validation of PDFF is still lacking for bone marrow applications. Purpose To determine the accuracy and precision of MRI‐determined vertebral bone marrow PDFF among different readers and across different field strengths and imager manufacturers. Study Type Repeatability/reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
1
27
1
1
Order By: Relevance
“…To account for this, in our study all CT and MRI scans were performed at the same respective unit with fixed scanning parameters. A recent report indicated a low level of bias across field strengths and imaging platforms for determination of fat content using MRI PDFF 29 . However, as this study used MRI PDFF to determine vertebral bone marrow fat content, it is not known if those results are directly transferable to myosteatosis measurements.…”
Section: Discussionmentioning
confidence: 99%
“…To account for this, in our study all CT and MRI scans were performed at the same respective unit with fixed scanning parameters. A recent report indicated a low level of bias across field strengths and imaging platforms for determination of fat content using MRI PDFF 29 . However, as this study used MRI PDFF to determine vertebral bone marrow fat content, it is not known if those results are directly transferable to myosteatosis measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study, by Schmeel et al (65), confirms vertebral marrow PDFF obtained by chemical shift-encoding based water-fat MRI as highly accurate, repeatable and reproducible among readers, filed strengths and MRI units, highlighting its value as a quantitative imaging biomarker.…”
Section: Water-fat Imagingmentioning
confidence: 81%
“…[21] and is hindered by the dynamic clinical presentation and by the lack of quantitative tools for measuring the composition of the underlying marrow. For example, previous studies reported that MC 1 and MC 2 are inter-convertible [22,23] and that approximately 20% of BML show characteristics of both MC 1 and MC 2 or MC 2 and MC 3 [24]. This confounds binary MC classification, which could partly explain why the size of any one type of MC may not directly correlate with symptoms [20].…”
Section: Discussionmentioning
confidence: 99%